Recreation, leisure and anthropotechnic (Impetus, 2021)
This paper aims to explain the sense of leisure as an anthropotechnic, which is a form of exercise whereby, man builds and modifies oneself. First, a problematization about the difference between recreation and leisure are going to be presented. Secondly, arguments in which the conception of idleness as anthropotechnic relies, are going to be shown, following in parallel, Seneca and Sloterdijk´s approaches. Finally, it concludes by affirming, that the study of leisure implies a way of life based on freedom and self-creation.